2016
DOI: 10.3390/bs6040023
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Relationships in Autism Spectrum Disorder: Perspectives of Individuals with ASD and Supporters

Abstract: This study explored 17 dyads of academically successful people with Autism Spectrum Disorder (ASD) and individuals who they identified as supportive. Qualitative methods, including in-depth interviews, participant observations, and document analysis, were used to study these supportive relationships. The purpose of the study was to develop a substantive grounded theory regarding supportive relationships within the lives of individuals with ASD. A dynamic model of supportive relationships emerged, with trust, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Positive changes in their interaction patterns were demonstrated when children with ASD who had previously exhibited problems with social interaction began playing more and getting along better with their siblings. Research has shown that the lockdown restrictions may have allowed families to be together over longer periods of time as they were no longer seeing other people or going to certain places (Robledo & Donnellan, 2016). Thus, changes in interaction patterns may be attributed to the child adjusting to their new routines at home and spending more time together in a more supportive and non‐conflicting environment either prior or during the initial stages of lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Positive changes in their interaction patterns were demonstrated when children with ASD who had previously exhibited problems with social interaction began playing more and getting along better with their siblings. Research has shown that the lockdown restrictions may have allowed families to be together over longer periods of time as they were no longer seeing other people or going to certain places (Robledo & Donnellan, 2016). Thus, changes in interaction patterns may be attributed to the child adjusting to their new routines at home and spending more time together in a more supportive and non‐conflicting environment either prior or during the initial stages of lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…This collaborative agreement between the therapist and the client about the goals and tasks of therapy will also support the preferences of ASD patients for predictable instruction and rules of conduct [22]. The development of a strong alliance between therapists and patients is thought to be especially important for effective intervention [23]. Another mediator is emotion regulation.…”
Section: Introductionmentioning
confidence: 92%
“…While initiating friendships can be a difficult process for autistic people, sustaining those relationships might be their most significant social challenge. When overcome, it results in greater success in daily life (Robledo & Donnellan, 2016). Participants describe the value of TTRPGs in building and strengthening relationships.…”
Section: Figure 2 Valuable Game Mechanics Discussed By Number Of Part...mentioning
confidence: 99%